Vulneración de los Principios Constitucionales que atentan el Bien Público Social de libre ingreso, permanencia y graduación en la Ley de Educación Superior - Rosa Elena, Cuenca Calva (2017)
Higher education has been the basic tool through which different societies have reached the scientific, economic and social development; accordingly the Ecuadorian state tries to ensure this through the principles as discussed in the execution of this study has not been properly applied, becoming free admission, retention and graduation in higher education on a matter of public interest to States. My study focuses on many candidates cannot enter a higher education due to the limitations established for entry as many are assigned to races not chosen for study so not being given their due permanence within universities giving some difficulties at the time of graduation. So the Constitution of the Republic protects that education is a right of people throughout their lives and an unavoidable duty of the state so that universal access, retention, mobility and graduation without discrimination was guaranteed.